Conditional Criminal Voices against the Defendants of Criminal Acts of Corruption in Principle Perspective Justice and Legal Guarantee - Ferry, Ferry; Kristanto, Kiki; Silam, Achmad Adi Surya G. (Budapest International Research and Critics Institute (BIRCI-Journal): Humanities and Social Sciences, 2021)
Corruption crimes that have been occurring widely, not only harm the state's finances, but also have been a violation of the social and economic rights of the community at large, so corruption crimes need to be classified as crimes whose eradication must be carried out extraordinarily. Every person convicted of corruption is sanctioned in accordance with the provisions of the laws and regulations. One form of sanctions imposed by judges related to corruption cases is the Conditional Criminal verdict, which means that the criminal does not need to live inside the Correctional Institution. The verdict is indeed the power of the judge guaranteed in the Law of Judicial Power as well as related to conditional criminality as stipulated in Article 14a of the Criminal Code, but in the Corruption Crimes Act, there is no mention of criminal threats with conditional criminals. In other similar cases, there is a judge's ruling that does not impose a conditional criminal sentence but provides a prison sentence for the accused of corruption, resulting in inconsistencies in the application of the law by the judge in sending the accused to corruption. Therefore, with a conditional criminal conviction will have implications on the principle of justice and legal certainty for convicted other corruption cases, as well as for the Government and society in general in preventing and eradicating corruption cases.